2001
DOI: 10.1038/35052063
|View full text |Cite
|
Sign up to set email alerts
|

Prions: health scare and biological challenge

Abstract: Although human prion diseases are rare, the incidence of 'new variant' Creutzfeldt-Jakob disease in the United Kingdom is increasing exponentially. Given that this disease is probably the result of infection with bovine prions, understanding how prions replicate--and how to counteract their action--has become a central issue for public health. What are the links between the bovine and human prion diseases, and how do prions reach and damage the central nervous system?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
84
0
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 86 publications
0
84
0
7
Order By: Relevance
“…The prion protein (PrP) is the causative agent of the transmissible spongiform encephalopathies (TSEs) that include CreutzfeldtJakob disease (CJD), Gerstmann-Scheinker-Straussler (GSS) disease, kuru and fatal familial insomnia in humans, bovine spongiform encephalopathy in cattle, and scrapie in sheep (4). In these diseases, the normal cellular form of PrP (PrP C ) undergoes a conformational change to the infectious form, PrP Sc .…”
mentioning
confidence: 99%
“…The prion protein (PrP) is the causative agent of the transmissible spongiform encephalopathies (TSEs) that include CreutzfeldtJakob disease (CJD), Gerstmann-Scheinker-Straussler (GSS) disease, kuru and fatal familial insomnia in humans, bovine spongiform encephalopathy in cattle, and scrapie in sheep (4). In these diseases, the normal cellular form of PrP (PrP C ) undergoes a conformational change to the infectious form, PrP Sc .…”
mentioning
confidence: 99%
“…Prion diseases are transmissible, fatal neurodegenerative diseases affecting animals and humans (1). The prototypical human prion disease, sporadic Creutzfeldt-Jakob disease (sCJD), is thought to originate in the CNS, and no significant accumulation of the infectious agent (the prion) is found in extracerebral compartments.…”
mentioning
confidence: 99%
“…PrP Sc is generated through a conformational transformation of PrP C and represents the major component of infectious prions (reviewed in Refs. [1][2][3][4]. PrP 1 is post-translationally modified by the attachment of two N-linked complex carbohydrate moieties (Asn 180 and Asn 196 ) (5-7) and a glycosylphosphatidylinositol (GPI) anchor at serine 231 (8) as well as by the formation of a disulfide bond between Cys 178 and Cys 213 .…”
mentioning
confidence: 99%
“…It has been found that the only specific marker for ER import of PrP is a cleaved N-terminal signal sequence (10). 2 Misfolding of PrP C in the cytosol or in the ER can induce neurodegeneration in the absence of PrP Sc . Neurotoxic properties of cytosolic PrP aggregates were observed after proteasomal inhibition in cultured cells or after the forced expression of cytosolic PrP in transgenic mice (15).…”
mentioning
confidence: 99%